THU0348 Assessment of Submandibular Gland Ultrasonography in Early-Stage Sjögren's Syndrome. (15th July 2016) - Hashimoto, N.; Uchiyama, S.; Kitano, M.; Nakazawa, T.; Iwasaki, T.; Hashimoto, T.
Abstract : Background: Sjögren's syndrome (SS) is a chronic inflammatory autoimmune disease characterized by lymphocyte infiltration in salivary and lacrimal glands. Recently, salivary gland ultrasonography proved valuable for the assessment of salivary gland involvement in SS and seemed to exhibit good diagnostic properties. We previously reported that submandibular gland ultrasonography (SGUS) is a useful noninvasive and inexpensive procedure for the evaluation of the structural changes of salivary gland involvement in SS patients (International Symposium on SS 2002, EULAR 2009, EULAR 2012, EULAR 2015). However, the usefulness of SGUS for the evaluation of early-stage SS patients with normal salivary flow was unknown. Objectives: The aim of this study was to examine the usefulness of SGUS in early-stage SS patients with normal salivary flow. Methods: We observed 9 non-SS patients with anti-SS-A antibodies sero-positive, 13 SS patients with low salivary flow (L/SS) and 16 SS patients with normal salivary flow (N/SS). SS was diagnosed according to the American College of Rheumatology (ACR) classification criteria for SS. SS was divided into two groups according to salivary flow using Gum test [L/SS (≤10mL/10min) and N/SS (>10mL/10min)]. All patients were examined RF, FANA, anti-SS-A/SS-B antibodies in serum and labial salivary gland biopsies for the diagnosis of SS. All patients were performed US scans by a single examiner who was blinded to the clinical data and used an US with a 7.5-MHz liner array transducer (SSA-350A; Toshiba, Tokyo, Japan). US staging scores were assessed by glandular size, inhomogeneity and contrast of diagastric muscle (0: normal, 1: mild, 2: moderate, 3: severe structural damage). PD grading scores were graded by pulsed wave pattern in power Doppler US at the internal SG facial arteries (0: normal, 1: intermittent wave pattern, 2: disappearance of wave pattern). Results: The whole salivary flow was significantly decreased in L/SS (4.4±2.8mL/10min) patients than in non-SS (19.0±7.6mL/10min, p<0.001) and N/SS (19.1±8.0mL/10min, p<0.001) patients. All patients were anti-SS-A antibodies sero-positive. There were no significant differences among non-SS, N/SS and L/SS patients in the frequency of sero-positive antibodies such as RF, FANA and anti-SS-B. However, the size of SG was significantly smaller in L/SS (216.1±59.7mm 2 ) than in non-SS (325.9±66.2mm 2, p<0.005) and N/SS (311.3±98.7 mm 2, p<0.005). US staging scores and PD grading scores were significantly higher in L/SS (2.85±0.38, 1.62±0.51) than in non-SS (0.89±1.05, 0.33±0.71, p<0.001) and N/SS (1.44±1.15, 0.44±0.51, p<0.001) patients. Conclusions: SUSG findings reflect salivary gland functions and is useful for the diagnosis of SS with low salivary flow but not for early-stage of SS patients with normal salivary flow. Disclosure of Interest: None declared